Swisher, Ed., John F. Kennedy - de Graaf, Lawrence (Teaching History: A Journal of Methods, 2002)
This is a classroom text anthology of secondary writing, with a few documents, on the presidency of John F. Kennedy and thus reflects some strengths and weaknesses of anthologies. A diversity of authors offers multiple points of view on different aspects of Kennedy’s administration. This is well done on civil rights, where Henry Fairlie and Allen J. Matusow offer contrasting insights, and in the chapter assessing Kennedy, where three authors highlight his policy weaknesses, character flaws, and contributions to liberalism. Anthologies can also be tools for interpretation and historiography.